Chetomin, targeting HIF-1α/p300 complex, exhibits antitumour activity in multiple myeloma - Viziteu, Elena; Grandmougin, Camille; Goldschmidt, Hartmut; Seckinger, Anja; Hose, Dirk; Klein, Bernard; Moreaux, Jerome (British journal of cancer, 2016)
Multiple myeloma (MM) is an incurable clonal plasma cell malignancy. The constitutive expression of HIF-1α in MM suggests that inhibition of HIF-1α-mediated transcription represents an interesting target in MM. As p300 is a crucial co-activator of hypoxia-inducible transcription, disrupting the complex HIF-1α/p300 to target HIF activity appears to be an attractive strategy. We reported that chetomin, an inhibitor of HIF-1α/p300 interaction, exhibits antitumour activity in human myeloma cell lines and primary MM cells from patients. Our data suggest that chetomin may be of clinical value in MM and especially for patients characterised by a high EP300/HIF -1α expression and a poor prognosis.